Early Diet Exposure Differentially Alters the Microbiota and Metabolites in the Distal Colon of Piglets Fed Human Breast Milk or Formula (P20-037-19). (13th June 2019) - Matazel, Katelin; Brink, Lauren; Chintapalli, Sree; Mercer, Kelly; Piccolo, Brian; Bowlin, Anne; Shankar, Kartik; Yeruva, Laxmi
Abstract: Objectives: Exclusive breast milk (HM) feeding has been shown to have better immune function than cow's milk formula (FM) feeding during infancy and childhood. We used a piglet model and demonstrated enhanced immune response in HM-fed piglets relative to cow's milk formula (FM) fed piglets. Microbiota likely drives this positive outcome therefore, utilization of this porcine model provides an opportunity to study the GI microbiota at specific time points under controlled dietary conditions. Thus, the primary aim of this study was to determine the microbial communities within the gastrointestinal tract of the piglet fed with HM or FM. Methods: From postnatal day 2 through 21, Dutch landrace piglets were randomized and fed an isocaloric diet of HM ( n  = 11; Mother's Milk Bank; Fort Worth, TX) or FM ( n  = 11; Simulac Advance). On day 21, contents from the distal colon were collected and assessed for 16S rRNA sequencing and metabolomics was assessed by LC-MS. Data analyses were conducted using standardized pipelines (QIIME 1.9, R, and MetaboAnalyst version 4). Results: No significant differences were observed in microbial alpha-diversity. However, we observed significant diet differences at phyla and genus taxonomic level in beta diversity ( P  = 0.008). Furthermore, we observed significantly higher abundance of Actinobacillus, Prevotella, Haemophilus, Campylobacter, Dorea, ( P  < 0.05) in HM-fed piglets in comparison to FM-fed piglets. In addition, HM-fed piglets were observed to have less Oscillospira, Ruminococcus, Turicibacter ( P  < 0.05). Metabolite data analysis revealed ten compounds with significant differences between diet groups ( P  < 0.05). In the FM-fed piglets Raffinose, suberic acid, folic acid, adipic acid, 2-phenylacetamide and ergothioneine were significantly higher relative to HM-fed piglets. Glutamic acid however, was elevated in the HM fed piglets compared to FM-fed piglets. Conclusions: Early exposure to different neonatal diets within a controlled environment leads to distinct differences in the beta-diversity and relative abundance of microbes and metabolites present within the distal colon of piglets. Future studies will examine the role of diet and its effects on bioregional areas of the GI tract and its impact on the immune system. Funding Sources: Funding for this project was provided by the USDA-ARS Project 6026-51000-010-05S and NIHP20GM121293.